Revision of Cran illia opaca in New Caledonia - Vázquez, Rubén; Gabriel y Galán, José María; Alfaya, Pedro; Vicent, María; Prada, Carmen (My University, 2021)
Cranfillia opaca is a fern species present in New Caledonia, for which a great variation in morphology is reported. Some other species such as Blechnum deplanchei have been proposed, but those were later synonymized with C. opaca. In this work, we have studied this taxon at both the morphological and the anatomical level, as well as its ecology and geographical distribution. We found differences between C. opaca s.s. and B. deplanchei in the morphology of the sterile and fertile fronds, in several morphoanatomical features such as trichome shape, length, and distribution, and length and/or shape of different structures of sporangia and spores. The distribution of both taxa was also different, but they are sympatric at some localities. The differences identified in this study support the recognition of both taxa, and the combination of Cranfillia deplanchei (Baker) Vázquez Ferreira & Gabriel y Galán, which we propose here. A new taxonomic description is provided for both species. © 2021 Universidad Complutense de Madrid. All rights reserved. Author keywords Anatomy; Blechnaceae; Cranfillia; New Caledonia; New combination; Taxonomy